Pauline’s Acceptance to White Beauty Standard and Its Impact on Her Self-esteem in Toni Morrison’s The Bluest Eye - NOVI SRIWULANDARI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
This study takes Toni Morrison’s The Bluest Eye as its subject and white beauty standard as its topic. It solely covers the three statements of problems that aim to reveal how white beauty standard is exposed to Pauline, how Pauline shows her acceptance to white beauty standard, and how Pauline’s acceptance to white beauty standard affects her self-esteem. The first statement of problem is answered by using the concept of white beauty standard. Then, the second statement of problem is answered by showing the evidences of Pauline actions as the form of her acceptance of white beauty standard. Last, the third statement of problem is answered by using the self-concept inventory which is then supported by the concept of cognitive distortion to reveal Pauline’s self-esteem. The analysis of this study reveals that the white beauty standard is exposed to Pauline through beauty images and education, both formal and informal that exists in her society. Pauline gladly accepts the white beauty standard through the lifestyle, beauty images, behavior, and education which she practices, imitates, and adjusts from her surroundings. Her acceptance of white beauty standard then destroys her self-concept that is proven by the great numbers of negative item shown in her self-description. The negative self-concept then leads her to having a low self-esteem, as proven by the distorted ways of thinking she practices such as overgeneralization, global labeling, filtering, polarized thinking, self-blame, personalization, control fallacies, and emotional reasoning. Keywords: ideal beauty image, self-description, self-concept, distorted thinking, lifestyle, education